Fault Zone Permeability Decrease Following Large Earthquakes in a Hydrothermal System - Zheming Shi; Shouchuan Zhang; Rui Yan; Guangcai Wang (Geophysical Research Letters)
Abstract Seismic wave shaking‐induced permeability enhancement in the shallow crust has been widely observed. Permeability decrease, however, is seldom reported. In this study, we document coseismic discharge and temperature decrease in a hot spring following the 1996 Lijiang Mw 7.0 and the 2004 Mw 9.0 earthquakes in the Balazhang geothermal field. We use three different models to constrain the permeability change and the mechanism of coseismic discharge decrease, and we use an end‐member mixing model for the coseismic temperature change. Our results show that the earthquake‐induced permeability decrease in the fault zone reduced the recharge from deep hot water, which may be the mechanism that explains the coseismic discharge and temperature responses. The changes in the hot spring response reflect the dynamic changes in the hydrothermal system; in the future, the earthquake‐induced permeability decrease should be considered when discussing controls on permeability.